Nursing applicants' reasoning skills and factors related to them: A cross-sectional study. (June 2021) - Vierula, Jonna; Hupli, Maija; Engblom, Janne; Laakkonen, Eero; Talman, Kirsi; Haavisto, Elina
Abstract: Background: The assessment of reasoning skills is recommended in undergraduate nursing student selection. Reasoning skills are crucial for sound decision-making, improving patient safety and are necessary from the very beginning of studies. Nursing applicants' reasoning skills based on the reasoning process have not been previously measured. Objectives: To assess undergraduate nursing applicants' reasoning skills and factors related to them. Design: A cross-sectional study. Setting and participants: Undergraduate nursing applicants (n = 1056, response rate 55.4%), who consented to the study and performed a joint electronic entrance examination to six Finnish Universities of Applied Sciences in spring 2019, participated in the study. Methods: The Reasoning Skills (ReSki) test, based on the steps of the reasoning process, was used, comprising three question sections (collecting information, processing information, and identifying the problem and establishing goals). Background variables were collected through a questionnaire and the Positive System Usability Scale (P-SUS). The data were analysed with descriptive statistics, Pearson correlation coefficients and analysis of covariance with Tukey's test in post-hoc multiple group comparisons. Results: Applicants' total reasoning skills mean scores were above the centre of the range of possible scores (2.72/4.5, SD = 0.80). The applicants scored higher in collecting and processing information than in identifying the problem and establishing goals. Standard deviations demonstrated variance between the applicants' ability. Age, gender, and previous education were statistically significantly related to applicants' reasoning skills. Previous work experience was statistically significantly related to success only in the step of identifying the problem and establishing goals. Conclusions: Nursing applicants' reasoning skills vary in the student selection phase. Applicants are less able to identify the problem and establish goals than to collect and process information. Vocational education does not necessarily develop adequate reasoning skills and thus prepare students for higher education studies. The results have implications for educational institutions and further research. Highlights: Nursing applicants' reasoning skills vary in the student selection phase. Identifying the problem and establishing goals is difficult for the applicants. Vocational education is not necessarily developing adequate reasoning skills.